Surface finishing of additively manufactured Inconel 625 complex internal channels : a case study using a multi-jet hydrodynamic approach - Nagalingam, Arun Prasanth (2022)
The surface roughness of components built using the laser powder bed fusion (L-PBF) process is poor. Surface finishing the internal channels of L-PBF components is a challenge. We propose a multi-jet hydrodynamic approach to enhance the surface finish quality of the internal channels. We investigate the hydrodynamic finishing on L-PBF Inconel 625 linear, stepped, and non-linear internal channels with diameters 5 to 1 mm and length up to 100 mm (replicating the geometries in rocket injectors, fuel nozzles, and cooling channels). The multi-jet hydrodynamic finishing approach improved the surface quality by 60–90 % (final Ra, Sa ≤ 1 μm and Rz, Sz ≤ 20 μm), using an abrasive concentration of ≤1 % in 15 min. of processing time. Areal surface texture parameters Sdr and roughness ratio r ≈1, evidenced the uniformity of the surface finish with dominant abrasive microcuts, regardless of the initial non-uniform additive manufactured surface. Most of the surface finished channels had excellent dimensional integrity and internal contour circularity. We then discussed the advancements required in metal additive manufacturing and internal surface finishing—to safely deploy L-PBF components with micro internal channels in fuel injection and fluid transfer applications.